Suplementação de fontes orgânicas de manganês e zinco em rações para larvas de tilápia do Nilo - Cardoso, Sara Ugulino (2022)
The objective of this study was to evaluate the growth, body indices, oxidative stress and expression of pro-inflammatory cytokines of tilapia (Oreochromis niloticus) larvae fed diets supplemented with organic zinc (Zn) and manganese (Mn). A total of 10,200 tilapia larvae were used, distributed in 51 black polyethylene boxes, the experiment was conducted in a completely randomized design in a 4x4 factorial structure, more the control, with three replications. The treatments consisted of feeding the larvae with diets supplemented with different levels of zinc (0, 40, 80, 120 mg kg-1) and manganese (0, 10, 30, 40 mg kg-1). Larvae were fed for 30 days, eight times a day ad libitum. Tilapia fed diets supplemented with 40 mg kg-1 of zinc and 10 mg kg-1 of manganese; 80 mg kg-1 zinc and 10 mg kg-1 manganese showed the highest (p<0.05) survival rate and highest growth rates. The expression of the TGF-β, IL 8, IL 10 and IFN-γ genes of these tilapias were also upregulated (p<0.05). On the other hand, those fed diets supplemented with 40 mg kg-1 of zinc and 0 mg kg-1 of manganese; 80 mg kg-1 of zinc and 0 mg kg-1 of manganese showed the highest (p<0.05) mortality rate and, due to the reduction in stocking density throughout rearing, consequently showed the highest growth. Zinc and manganese levels did not influence intestinal length, hepatosomatic and viscerosomatic indices (p>0.05). Hepatic catalase, superoxide dismutase, lipoperoxidation and protein carbonylation activities were not altered (p>0.05). Only glutathione s-transferase activity showed an individual effect of zinc, with the lowest activity (p<0.05) for tilapia fed diets supplemented with 80 mg kg-1 of manganese. The use of organic mineral premix with zinc and manganese promoted gains in animal growth, increase in innate immunity resulting in greater survival of fish.